The influence of curing and surface preparation on the adhesion of protective coatings on concrete - Benn, Bernard Thomas (My University, 2010)
In cases where concrete has to be repaired or protected due to exposure to an aggressive environment, a protective coating is often used. The guidelines referenced on the subject of repairs and coatings of concrete require the substrate must be clean, dry and free from loose material but no mention is made of a preferred method of surface preparation. This research report presents details of an investigation in which concrete was subjected to different curing regimes in order to induce different qualities of surface concrete. The different surface qualities were prepared using four alternative surface preparation methods prior to coating. After an initial investigation, five different coatings were chosen in order to cover a broad spectrum of coatings available to the construction industry. Once the applied coatings had cured they were tested using a pull-off testing device to determine the adhesion properties. The mode of failure was determined by visual examination. In addition, surface characteristics were determined using an optical microscope and the water sorptivity test. Results indicate that preparing the surface before application of coatings does improve adhesion. The preparation that was easiest to carry out, and which also gave the best adhesion results, was the wire brushing technique. Considering the practicality for site application, the mechanical method would be most appropriate. From the findings, aliphatic coating exhibited the best adhesion properties, while epoxy resin and cementitious-based materials also gave satisfactory results. B T Benn 7231599 iii Elastomeric coating with lower adhesion strengths at early ages may be suited to surfaces that are expected to crack, as the elastic nature of the material will bridge the gap. Masonry paint, which was only used for comparative purpose did not perform as well as expected and had the lowest bond strengths. Where the removal of defective concrete is likely to result in a rough surface the cementitious material may be preferable.